IMPLEMENTASI REGULASI PENYIARAN AGAMA DI KOTA MAKASSAR - Akmal Salim Ruhana (Jurnal Dialog, 2015)
Religious broadcasting remains one of the most crucial topics in inter-religious relationship. When Islamic dawah and Christian missionary share the same fields, a potential conflict and competition occurs. Indonesian government regulates this issue by issuing The Joint Decree of the Minister of Religious Affairs and the Minister of Home Affairs No.1 year 1979 on the Procedures of Religious Propagation and Foreign Aids to Religious-based Organization in Indonesia. This decree, which was regarded as outdated by some parties, is facing the challenges of the more dynamic society. Thus, it needs some updates or revisions for the decree. This study attempts to explore the implementation of this joint decree by collecting the responses from the society. By employing literature review, interviews, and observations, this study takes form of descriptive analytical method. It is found that there are no more religious conversion tricks by offering incentives such as: money, gifts, or clothing in Makassar. Meanwhile, foreign aids or facilities are not detected and recorded by the local authorities therefore they are out of control.